PENGEMBANGAN MEDIA PEMBELAJARAN SISTEM PEREDARAN DARAH PADA MANUSIA BERBASIS AUGMENTED REALITY - Ananda Putri Zafira; Tri Widodo (Jurnal Pendidikan Teknologi Informasi (JUKANTI), 2025)
Developments in the field of information technology are currently experiencing very rapid increases. The use of information technology is not only in the business world, but also in the public sector. One institution that utilizes information technology is a school institution. In the world of education, there are many multimedia applications for learning. Both in the form of applications and learning media that can support students' ability to understand learning. This research discusses the development of augmented reality-based learning media for the circulatory system in humans. Which aims to broaden students' insight into augmented reality technology and make learning more interesting so that it can increase student motivation in the learning process. This development uses the ADDIE- Analysis, Design, Development, Implementation, Evaluation method. The media has been tested for suitability by media experts who obtained 83.93% very good results, then material experts who obtained 94.64% very good results, and respondents who obtained 90.75% very good results.